PENGARUH PENERAPAN MODEL PEMBELAJARAN BERBASIS PROYEK TERHADAP PENINGKATAN LITERASI LINGKUNGAN DAN PERILAKU RAMAH LINGKUNGAN GREEN BEHAVIOR SISWA SEKOLAH DASAR - Hairul Uyun; Encep Supriana; Ni Made Winursiti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the influence of the implementation of project-based learning models in improving environmental literacy, green behavior, and environmental awareness among third-grade students at SDN Warnasari Elementary School. Through the "My Trash, My Treasure" project, students were invited to understand the concept of waste sorting, identify types of waste, and practice waste sorting in school and home environments. This study used a quasi-experimental method with a pre-test and post-test design. The results showed a significant increase in students' understanding of waste sorting and an increase in green behavior in carrying out waste sorting. The factors that support the success of this learning model include student motivation, teacher support, the availability of facilities, and parental involvement. The challenges faced and the proposed solutions are also discussed in this study.